Validitas Buku Ajar Berbasis STEM-Cp Materi Elastisitas dab Hukum Hooke Untuk Melatih Keterampilan Berpikir Kritis Siswa Kelas XI SMA - Febriyanti, Melisa Putri; Permatasari, Ika; Maryani, Maryani; Ningrum, Tika Widiya; Silvira, Lia; Andianti, Putri Wihatma; Pyrenia, Adisty; Wulandari, Pria Nur (Jurnal Ilmiah Wahana Pendidikan, 2024)
Critical thinking is a higher-order thinking skill that can improve students' critical analysis power. The use of the STEM-CP approach can facilitate students to develop skills in the 21st era. The purpose of this study was to examine the validity of STEM-CP-based textbooks, elasticity material and hooke's law to train students' critical thinking skills. The method used in this research is research and development using the ADDIE development model with 5 stages, including the analysis stage, planning stage, development stage, implementation stage, and evaluation stage. The results of the research conducted, this textbook was declared valid with the average percentage for aspects of construction, presentation, language, and graphics respectively were 96%, 97.33%, 93.33%, and 96.66%. The total percentage of overall aspects of the three validators is 95.83%. Referring to the book notability criteria in the table, this result is stated as a "very decent" category. Based on this, STEM-CP-based textbooks on elasticity material and hooke's law can be implemented in learning and attract students to learn the material, so it is expected to improve students' thinking skills on elasticity physics and hooke's law.